Investigation on NSM-CFRP Ropes Shear Strengthened RC Beams with an Inclusion of Steel-reinforced Geopolymer in the Compressive Zone - Sudibyo, Gathot Heri; Tudjono, Sri; Nurhuda, Ilham (Periodica Polytechnica Civil Engineering, 2024)
The field of structural engineering was focused on the growth of the latest technologies, materials, and techniques that promoted sustainability, and the use of Carbon Fiber Reinforced Polymer (CFRP) as well as geopolymer was a prime example of this effort. Several investigations and developments in composite materials have generated a wide range of materials that could be used to enhance the strength and durability of structures. This study introduces a novel approach to shear strengthening of reinforced concrete (RC) beams by utilizing Near Surface Mounted (NSM) CFRP ropes in combination with steel-reinforced geopolymer in the compressive zone. The investigation aims to assess the effectiveness of these advanced composite materials in enhancing the structural performance of RC beams, as opposed to conventional steel rebar. Three specimens were subjected to three-point bending tests, demonstrating that the NSM-CFRP ropes, paired with steel-reinforced geopolymer, significantly increased load-carrying capacity. Additionally, the results indicated substantial improvements in ductility and energy absorption. This research contributes to the field by providing a sustainable and efficient alternative to traditional strengthening techniques, supported by a comprehensive assessment of both experimental and numerical findings.